2016
DOI: 10.1080/03091902.2016.1209589
|View full text |Cite
|
Sign up to set email alerts
|

Heart sound and lung sound separation algorithms: a review

Abstract: Breath and cardiac sounds are two major bio sound signals. In this, heart sounds are produced by movement of some body parts such as heart valve, leaflets and the blood flow through the vessels, whereas lung sounds generates due to the air in and out flow through airways during breathing cycle. These two signals are recorded from chest region. These two signals have very high clinical importance for the patient who is critically ill. The lung functions and the cardiac cycles are continuously monitored for such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Accordingly, the participant anesthesiologists were asked to rate the difficulty of operating the device during the auscultation on a scale of 0 to 10 (0: not difficult at all; 6: occasional difficulty during the test period; 10: extremely difficult during the test period). Furthermore, because the heart sound and lung sound are 2 major body sound signals from the chest region and often interfere with each other during auscultation, manufacturers provide unique algorithms for the separation of heart and lung sound ( 8 ). Therefore, lung sound quality in the questionnaire referred to the quality of the heart and lung sound separation during auscultation (0–10; 0: heart sound was comparable to or more obvious than lung sound with frequent heart sound interference during auscultation; 6: partial sound separation with occasional heart sound interference during auscultation; 10: complete sound separation without detectable heart sound during lung sound auscultation).…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, the participant anesthesiologists were asked to rate the difficulty of operating the device during the auscultation on a scale of 0 to 10 (0: not difficult at all; 6: occasional difficulty during the test period; 10: extremely difficult during the test period). Furthermore, because the heart sound and lung sound are 2 major body sound signals from the chest region and often interfere with each other during auscultation, manufacturers provide unique algorithms for the separation of heart and lung sound ( 8 ). Therefore, lung sound quality in the questionnaire referred to the quality of the heart and lung sound separation during auscultation (0–10; 0: heart sound was comparable to or more obvious than lung sound with frequent heart sound interference during auscultation; 6: partial sound separation with occasional heart sound interference during auscultation; 10: complete sound separation without detectable heart sound during lung sound auscultation).…”
Section: Methodsmentioning
confidence: 99%
“…For this purpose, 207 recordings were filtered with a 4 th -order Butterworth bandpass filter with passband frequencies 50-250 Hz and 200-1000 Hz, in order to separate heart and lung sounds, respectively. This is a commonly used approach to improve signal quality in commercial stethoscopes and clinical studies, with passband frequencies based on the main frequency bands reported in literature for neonatal heart and lung sounds [17].…”
Section: A Data Acquisition and Preprocessingmentioning
confidence: 99%
“…Our network design is inspired by the fundamental nature of heart sounds and their applicability in a real-world setting. The heart sound signal is quasi-periodic as it is generated at regular intervals by sequential opening and closing of heart valves as blood flows through heart chambers [22]. Therefore, we hypothesize that a recurrent module in the network will improve denoising performance compared to standalone convolutional models because of its capability to identify temporal relationships.…”
Section: Introductionmentioning
confidence: 99%